Contact Analysis on The Whole Frame of 32.8MN PRESS - Zhicheng Huang; Nanxing Wu; Xingguo Wang (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Automatic hydraulic press is one of the key Ceramic machinery and equipments for pressing ceramic wall and floor tiles, and its frame withstands all of the work force when it works, so the work performances of the frame have an important impact on the structural performance of the entire automatic hydraulic press. Took the frame of 32.8MN automatic hydraulic press as research object, established its three-dimensional model through Pro/Engineer software and carried on contact finite element analysis for it by using the large commercial finite element software ANSYS to gain the stress and strain distribution of the frame, and then carried out a detailed analysis of the results. The work done can help to fully understand the structure properties of existing automatic hydraulic press and serve as guidance to further improve its performance, and at the same time provide a theoretical basis for the structural design of the same type of automatic hydraulic press frame. DOI: http://dx.doi.org/10.11591/telkomnika.v11i7.2836